School Refusal in Youth: A Systematic Review of Ecological Factors. - Leduc, Karissa; Tougas, Anne-Marie; Robert, Virginie; Boulanger, Camille (Child Psychiatry & Human Development, 2024)
To guide school practitioners in the identification and intervention of youth with anxious school refusal, this systematic review used an ecological lens to examine the factors that differentiated children and adolescents with school refusal from those without. Based on the rigorous protocol from the Center for Reviews and Dissemination's (CRD) internationally recognized guidelines, 15 studies examining 67 different factors were identified. Results reveal 44 individual, social and contextual factors that differentiate youth with school refusal from peers without school refusal. Findings highlight the centrality of anxiety, or anxiety-related symptoms, and diverse learning needs as main points of contrast between youth with school refusal and those without. Implications of an ecological understanding of the factors associated with school refusal for selective and indicative prevention by school and mental health practitioners are discussed.